Living trophies: trees, triumphs, and the subjugation of nature in early Imperial Rome - Fox, Andrew (2019)
The aim of this thesis is to examine the cultural significance of trees in Rome and its environs, with a focus on the early Principate. While arboreal studies are prominent in studies of the pre- and post-classical periods, discussion of trees in the Greco-Roman world have been concentrated primarily in a religious context. The thesis exploits the approaches established by post-classical history, geography, and classical studies to explore the role of trees outside of a religious context, focussing primarily on the role of trees as living natural monuments of the city’s triumphal past. Chapter One presents an overview of Roman attitudes to trees in Rome, from the origins of trees and their role in the establishment of civilisation to Roman interactions with them in the city. The second chapter focusses in from the broad overview offered in Chapter One and examines the discussion of trees in Pliny’s Natural History, and how that discussion is influenced by Pliny’s broader narrative purpose. Chapter Three continues the focussed discussion, and considers trees in the context of triumphal Trajanic architecture, which commemorates victories over heavily-forested territories. Chapter Four discusses the role of trees in the triumphal procession, and the use of trees and their constituent parts to communicate messages of conquest, fertility, and piety. The final chapter explores the key challenges of natural monuments, from their vulnerability to human intervention to their changing and mortal nature, and the thesis closes with a discussion of how the death of such a monument is approached in three examples of monumental trees. Through these chapters, this thesis aims to expose a nuanced relationship with trees in the Roman world, and to place this relationship in the context of the politics of victory and empire building that dominated the collapse of the Republic and rise of the Principate.